Implementation Forms Of Integration Strategy For Development Of Shipyard Industry In Surabaya And Surrounding - Bawias, Ishak; Zubaydi, Achmad; Ma'ruf, Buana (Wave: Jurnal Ilmiah Teknologi Maritim, 2017)
One of the successes of the Philippines and Vietnam in developing the shipbuilding industry is by applying integration strategies within the  shipbuilding industry, so that synergy between docks and supporters is optimized and create sustainable competitiveness. Therefore, this research is aimed at developing shipyard industry in Surabaya and its surroundings, through analysis of business competitiveness with the implementation of integration strategies. The form of strategy implementation from several previous studies was continued through questionnaires (based on Likert Scale) to 31 respondents of top management of a number of shipyard and supporting industries, as well as related institutions. The result, then analyzed by using Quantitative Strategic Planning Matrix (QSPM), so that obtained some form of synergy and potential synergy pattern done in shipbuilding industry development.